GEPSdb: The Gene Expression Database of Poplar under Stress. Issue 1 (8th December 2021) - Liu, Shifan; Wang, Zihao; Lan, Yangang; He, Ting; Xiong, Rui; Wu, Caijuan; Xiang, Yan; Yan, Hanwei
Abstract: As a model tree species, poplar ( Populus L.) has important economic and ecological value. Here, we constructed the GEPSdb (Gene Expression Database of Poplar under Stress; http://gepsdb.ahau‐edu.cn/ ), which is an integrated database of poplar gene expression profiles derived from RNA‐seq and microarray library data. This database provides a comprehensive collection of gene expression data from poplar exposed to 14 types of environmental stress from 11 high‐quality RNA‐seq experiments and 51 microarray libraries. The GEPSdb includes 56 genes from previous literature that have been examined in poplar and functionally verified. By incorporating data from numerous expression analyses, GEPSdb provides a user‐friendly web interface for querying, browsing, and visualizing the expression profiles of related genes. Consequently, GEPSdb can be used to link transcription data with phenotypes and can enhance our understanding of important biological processes and mechanisms underlying complex agronomic traits in poplar. Core Ideas: Gene Expression Database of Poplar under Stress (GEPSdb) is the first gene expression profile database for poplar under stress. GEPSdb can link transcription data with phenotypes. GEPSdb integrates an abundance of data from public RNA‐seq and microarray libraries.